Penerapan Model Pembelajaran Problem Based Learning Berbantuan Media UTAWIS untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Maharani, Virka Arditya Pramesti; Nugraheni, Luthfa; Ardianti, Sekar Dwi (FKIP Universitas Wisnuwardhana, 2024)
Evaluation of the effectiveness of the implementation of the problem-based learning (PBL) model integrated with multimedia-based learning media (UTAWIS) in improving the critical thinking skills of fifth grade students as well as the pedagogical competence of Natural and Social Sciences (IPAS) teachers in schools elementary school involving 22 grade IV students from SD Negeri 6 Jekulo, Kudus, this research was carried out in several cycles. Data was collected triangulatedly through observation, in- depth interviews, documentation, and critical thinking ability tests, then analyzed qualitatively and descriptively quantitatively. The research results showed significant improvements in both students' cognitive aspects, which were measured through increased test scores, and affective aspects, such as student interest and involvement. In addition, teacher competence to design learning models that focus on students has increased significantly. These findings indicate that the integration of the PBL model with UTAWIS media is an effective alternative for improving the quality of science and science learning at the elementary school level. The practical implications of this research highlight the need to develop more intensive teacher training programs related to the implementation of the PBL model and the use of technology in learning. In addition, curriculum development that integrates the PBL model more systematically is also recommended. This research provides strong empirical evidence regarding the potential of this learning approach in improving the quality of education in primary schools and forms the basis for further research to test the generalizability of these findings in different contexts.